Why do the Russians succumb to the "strong-hand" government? Historical-cultural legitimacy of the Russian state leadership in the context of Yuri Pivovarov`s theory = Dlaczego Rosjanie poddają się rządom "silnej ręki"? Historyczno-kulturowa legitymizacja przywództwa państwowego Federacji Rosyjskiej w kontekście teorii Jurija Piwowarowa - Olędzka, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
State leadership in Russia is determined by historical and cultural as well as by legal and institutional premises. !e analysis of ways of obtaining legitimacy by state leaders of the Russian Federation is a borderline issue of political science, sociology, and history.
Keywords: legitimization of power; legitimacy of the leadership of the state; Russian Federation; archetypes of power in Russia; legitymizacja władzy; legitymizacja przywództwa państwowego; Federacja Rosyjska; archetypy władzy w Rosji